The Significance of Military Expenditure, Tourism, and Exports for Sustainable Economic Growth - Aziz, Ghazala; Alsaggaf, Majid Ibrahim; Khan, Mohd Saeed (Frontiers in Environmental Science, 2021)
The current empirical study addresses the recent economic of Saudi Arabia, such as the uncertainly of economic growth, dependence on oil export. For this purpose, labor, capital, oil price, terrorism, military expenditure, tourism, and exports are added to the analysis. ARDL long-run, and short-run analysis are used, the results of the study have revealed that labor is negatively related to economic growth which suggests that efforts should be done to reduce dependence on international labor through the installation of production facilities in those countries where labor is cheap. Also, it is noted that capital, tourism, and non-oil exports enhance economic growth whereas oil price is the main problem for economic growth of the country. These results suggest that diversification of exports to non-oil products is a good strategy to boost economic growth. Alongside, domestic tourism should be promoted to enhance its share in economic activities. The current study helps the policy makers to open new earing avenues such as, enhance tourism sector, modernize the industries which helps in technology exports etc.